Higher Education in 2040 : A Global Approach - Zwaan, Bert van der, 1952-; Project Muse; Project Muse. (Baltimore, Maryland : Project Muse, 2019)
Since the Middle Ages, universities have displayed impressive resourcefulness in their ability to adapt to the changing dynamics and demands of their times. But in the last fifty years, the landscape of higher education - with the emergence of online and mass education, skyrocketing tuition, and a controversial system for ranking institutions - has begun evolving so rapidly and profoundly that the concept of the university now needs to be rethought. This book explores the future of modern higher education by looking at it on a global scale. Bert van der Zwaan compares European developments with those taking place in North America and Asia to argue that the phoenix of an entirely new type of university will rise from the ashes of the classical system: less tied to buildings and set locations, the new university will embed itself more deeply in society by offering innovative forms of digital knowledge and making customized teaching available on demand. A timely discussion of a topic whose worldwide impact continues to grow, this is essential reading for anyone concerned about the state of higher education - both for today's students and in the decades to come.
Preface -- Introduction: a sinking ship? -- pt. 1. Ancient problems and modern dilemmas -- The idea of a university -- A history of secularization and democratization -- Grappling with change -- Rising costs, selection and governments in retreat -- On size, bureaucracy and distrust -- The successes and failures of the entrepreneurial university -- Under the spell of production and quality -- pt. 2. The key factors in the coming decades -- The key trends -- The economy determines the future -- Urbanization and global knowledge hubs in 2040 -- Information technology as a disruptive force -- Digital or campus teaching? -- The labour market and lifelong learning -- The civic university -- pt. 3. Contours of the university of the future -- Quid durat? -- The need for legitimization -- Old and new core values -- The government and the higher education system of the future -- The global university and the knowledge ecosystem of the future -- How will the comprehensive research university survive? -- The curriculum of the future -- Conclusion: the transition to 2040 -- Bibliography.
Translation of: Haalt de universiteit 2040?
Issued as part of book collections on Project MUSE.
Includes bibliographical references (pages 247-255).
Description based on print version record.
Keywords: Higher education and state -- European Union countries; Electronic books